Genotyping of Histological Cutaneous Leishmaniasis Isolated by Dental Broach Smear in Iraqi Patients - Salah Mahdi Hassan; Bushra Qasim Dhumad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cutaneous leishmaniasis is a major public health problem as a disease endemic in Iraqi population. Manydiagnostic tools are used to establish the diagnosis like smear, histopathology and culture. To find morerapid, sensitive and specific diagnostic method for the diagnosis of cutaneous leishmaniasis, and to detectthe genotypes of leishmania tropica and leishmania major strains in Iraq. Sixty six patients (43 males and23 females) with clinical diagnosis of cutaneous leishmaniasis were included in present work during theperiod between December / 2019 to May / 2020 in Al-Yarmook Teaching Hospital and Al-Karama TeachingHospital. The age of patients ranged from 6 months to 55 years, with median age 24 years. The followingdiagnostic techniques were carried out for diagnosis of cutaneous leishmaniasis including dental broachsmear, histopathology examination and culture on Roswell park medium institute (RPM I 1640) and onNNN media. In addition to polymerase chain reaction (PCR) and restriction fragment length polymorphism(RFLP), genotype techniques were performed for all patients. Sixty patients with other skin lesions wereprocessed for PCR as a control group.